Analysis of the Robustness of Islamic Commercial Banks in Indonesia during the Covid-19 Pandemic - Fitra Rizal (Journal of Islamic Economics and Finance Studies, 2022)
AbstractCovid-19 impacts various sectors of people's lives, including the Islamic finance sector. This study aims to determine the robustness of Islamic Commercial Banks during the Covid-19 pandemic using the Risk-Based Bank Rating (RBBR) method or better known as the RGEC method covering the Risk Profile, Earning, and Capital of Islamic Commercial Banks in Indonesia from January 2019 to December 2021. The type of research in this study is descriptive research with a qualitative approach. The results showed that the average NPF ratio was 2.98%, indicating that the Islamic Commercial Banks were robust. The average ROA ratio of 1.56% indicates that the Islamic Commercial Banks are in a very robust condition. And the average CAR ratio of 22.64% indicates that the Islamic Commercial Banks are in a very robust condition. This fact shows that the robust condition of Islamic commercial banks in Indonesia during the Covid-19 pandemic is very robust and stable. AbstrakCovid-19 benar-benar memberikan dampak di berbagai sektor kehidupan masyarakat, termasuk sektor keuangan syariah. Penelitian ini bertujuan untuk mengetahui tingkat kesehatan Bank Umum Syariah (BUS) Indonesia selama masa pandemi Covid-19 dengan metode Risk Based Bank Rating (RBBR) atau yang lebih dikenal sebagai metode RGEC mencakup Risk Profile, Earning dan Capital BUS di Indonesia dari Januari 2019 sampai Desember 2021. Jenis penelitian dalam penelitian ini adalah penelitian deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa, rata-rata rasio NPF sebesar 2,98% menunjukkan bahwa BUS dalam kondisi yang sehat. Rata-rata rasio ROA sebesar 1,56 % menunjukkan bahwa BUS dalam kondisi yang sangat sehat. Dan rata-rata rasio CAR sebesar 22,64 % menunjukkan bahwa BUS dalam kondisi yang sangat sehat. Fakta tersebut menunjukkan bahwa kondisi kesehatan Bank Umum Syariah di Indoneseia pada masa pandemi Covid-19 sangat sehat dan stabil.